Warden Oom, Regionalist: Authorial Ethos, Generic Functions - Lambrecht, Bram (Werkwinkel, 2016)
Recent scholarship in Dutch literature of the interwar years has revalued to an important degree the genre of regional or rural literature. Whereas existent research in this field mainly zooms in on the thematic motives and rhetorical structures of the regional text, this paper aims at combining a textual and contextual approach. It hopes to do so by linking the functions of the regional genre to the construction of the regional author’s ethos or authority outside his oeuvre. One author here functions as a representative case in point: Warden Oom (Edward Vermeulen), a once successful but now forgotten Flemish folk writer and regionalist. This paper analyzes how Vermeulen, in autobiographical documents and interviews, embodies both an encyclopedic and an artistic authority. These two forms of extra-literary authority are a means to guarantee, so the argument goes, the efficacy of the informative and documentary as well as the esthetic functions of Vermeulen’s regional oeuvre. In this way, this paper not only pays attention to the rarely documented and therefore highly neglected voice of the regional author himself but it also grasps these autobiographical writings to situate the regional text in its broader context. Moreover, this article’s focus on the esthetic ambitions and functions of the regional author and his oeuvre may shed a new light on a genre which is usually considered to be heteronomous in the first place.